Longitudinal Effects of Engagement with Workplace Health Programmes on Employee Outcomes: A Relational Perspective. (19th November 2021) - Fida, Roberta; Game, Annilee; Stepanek, Martin; Gendronneau, Cloé
Abstract: Organizations increasingly adopt health and wellbeing programmes (HWPs), yet little is known about the underlying processes or boundary conditions that may influence the effectiveness of these initiatives on employee outcomes such as wellbeing and job satisfaction. In a 3‐year study, we adopted a social exchange approach to examine: (1) the role of relational context in mediating the links between employee engagement with HWPs and wellbeing and job satisfaction over time and (2) whether organizational prioritization of HWPs moderates the relationship between engagement with HWPs and quality of relationships at work. The results of our multilevel and longitudinal structural equation model (N = 7, 785 UK employees, nested within 64 organizations) showed that the more employees engage with HWPs, the better the quality of co‐worker relationships, the less they experience bullying over time and the better their longer‐term wellbeing and job satisfaction. Against expectations, organizational prioritization of HWPs did not moderate the link between HWPs engagement and perceived co‐worker relationship quality. Theoretical and practical implications of the study are discussed.